Calibration study of dual-band Weaver–Hartley receiver architecture. Issue 6 (June 2015) - Elmala, Mostafa A.I.; Ibrahim, Ghada H.
Abstract This paper presents a calibration study of dual-band image rejection receiver based on combined Weaver–Hartley architecture, with improved image rejection of first and second image signals. The system implementation is based on dual-band WLAN 802.11 a/g. When the desired signal is at 5.7-GHz band, the 2.4-GHz band becomes the first image signal and vice versa. The output IF frequency is at 30-MHz. The detection of the gain and phase mismatches is based on modeling, extraction of related error signals and correcting them in closed loop. Moreover, we demonstrate an open loop technique to reach the phase and gain correction signals. The correction signals can be digitally stored and applied as digital trimming control on the LO signals. Simulation showed close to 60 dB of image rejection ratio for the first image signal. Second image signal is rejected by a 4-section poly-phase filter.